Register to reply

4th order differential equation

by chuy52506
Tags: differential, equation, order
Share this thread:
chuy52506
#1
Nov19-12, 10:20 PM
P: 77
I'm trying to find the gen. solution to the equation y''''-8y'=0
I found the characteristic polynomial by plugging in ert as a solution to y.
I got,
r^4-8r=0
I simplified to get
r*(r^3-8)
Thus one root is 0, for the other 3 i must find the cubed root of 8.
I know the answer is 2*e2m*pi*i/3 for m=0,1,2
How do I arrive at that answer?
I tried the following:
Represent 8 as 8=8[cos(2*pi)+i*sin(2*pi)]=8*ei*pi
Phys.Org News Partner Science news on Phys.org
'Office life' of bacteria may be their weak spot
Lunar explorers will walk at higher speeds than thought
Philips introduces BlueTouch, PulseRelief control for pain relief
haruspex
#2
Nov19-12, 11:32 PM
Homework
Sci Advisor
HW Helper
Thanks
P: 9,928
Quote Quote by chuy52506 View Post
I'm trying to find the gen. solution to the equation y''''-8y'=0
I found the characteristic polynomial by plugging in ert as a solution to y.
I got,
r^4-8r=0
I simplified to get
r*(r^3-8)
Thus one root is 0, for the other 3 i must find the cubed root of 8.
I know the answer is 2*e2m*pi*i/3 for m=0,1,2
How do I arrive at that answer?
I tried the following:
Represent 8 as 8=8[cos(2*pi)+i*sin(2*pi)]=8*ei*pi
It should be 8 = 8ei*2πm, for any m, right?
chuy52506
#3
Nov20-12, 12:01 AM
P: 77
The roots are r=0,2*e(2*m*pi*i)/3
then it says this is equivalent to
r=0,2,-1+i*sqrt(3),-1-i*sqrt(3)

Then the gen solution is
y=c1+c2*e2*t+e-t*[c3*cos(t*sqrt(3))+c4*sin(t*sqrt(3))]

I dont know how they arrive to this

JJacquelin
#4
Nov20-12, 12:34 AM
P: 761
4th order differential equation

Obviously, the cubic root of 8 is 2.
r^4-8r = r(r-2)(rē+2r+4)
= r (r-2) [r+1+i sqrt(3)] [r+1-i sqrt(3)]
haruspex
#5
Nov20-12, 02:16 AM
Homework
Sci Advisor
HW Helper
Thanks
P: 9,928
Quote Quote by chuy52506 View Post
The roots are r=0,2*e(2*m*pi*i)/3
then it says this is equivalent to
r=0,2,-1+i*sqrt(3),-1-i*sqrt(3)

Then the gen solution is
y=c1+c2*e2*t+e-t*[c3*cos(t*sqrt(3))+c4*sin(t*sqrt(3))]

I dont know how they arrive to this
Suppose λ is a root of the polynomial. That is, the differential equation has a factor (D-λ), where D = d/dt, so the equation can be written P(D)(D-λ)y = 0, for some polynomial P.
Try the solution y = eλt: P(D)(D-λ)eλt = P(D)(D(eλt - λeλt) = P(D)(λeλt - λeλt) = 0. So the general solution is a linear combination of such terms.
A complication arises when there is a repeated root, i.e. a factor (D-λ)n. It's fairly easy to show that treλt is also a solution for r = 1, .. n-1.
chuy52506
#6
Nov20-12, 03:20 AM
P: 77
But where is the root e(2*m*pi*i)/3 derived from? and how is this equivalent to the roots:2,-1+i*sqrt(3),-1-i*sqrt(3) for m=1,2,3
lurflurf
#7
Nov20-12, 04:30 AM
HW Helper
P: 2,264
exp(2∏n i)=1
so
(exp(2∏n i/3))^3=1
also
exp(2∏n ix)=cos(2∏n x)+i sin(2∏n x)
so
exp(2∏n i/3)=cos(2∏n /3)+i sin(2∏n /3)
haruspex
#8
Nov20-12, 04:37 AM
Homework
Sci Advisor
HW Helper
Thanks
P: 9,928
Quote Quote by lurflurf View Post
exp(2∏n i)=1
so
(exp(2∏n i/3))^3=1
also
exp(2∏n ix)=cos(2∏n ix)+i sin(2∏n ix)
so
exp(2∏n i/3)=cos(2∏n i/3)+i sin(2∏n i/3)
Small correction (too many i's):
exp(2∏n ix)=cos(2∏n x) + i sin(2∏n x)
so
exp(2∏n i/3)=cos(2∏n/3) + i sin(2∏n/3)

... and cos(2∏/3) = -cos(∏/3) = -(√3)/2 etc.
Jim Kata
#9
Nov21-12, 01:10 AM
Jim Kata's Avatar
P: 233
Quote Quote by chuy52506 View Post
But where is the root e(2*m*pi*i)/3 derived from? and how is this equivalent to the roots:2,-1+i*sqrt(3),-1-i*sqrt(3) for m=1,2,3
What you are getting confused about is the field of the reals vs. the field of complex numbers. Over the field of the reals there is only one solution to the equation r^3-8=0 namely r=2, but over the field of complex numbers there are 3 distinct solutions to the equation r^3-8=0.

To see this understand that [tex]exp(i2m\pi)=1[/tex] for any [tex]m\epsilon\mathbb{Z}[/tex]. So if, [tex]r^3=8\cdot1=8exp(i2m\pi)[/tex] then
[tex]r =2exp(\frac{i2m\pi}{3})[/tex] but you can see the only distinct ones are for m= 0,1,2 since for m beyond or below that you repeat your answers. To answer your other question you need to know about Euler's formula which says that: [tex]e^{i\phi}=cos(\phi)+isin(\phi)[/tex]

So for example, [tex]2exp(i\frac{2\pi}{3})=2(cos(\frac{2\pi}{3})+i\sin({\frac{2\pi}{3}})=2(-\frac{1}{2}+i\frac{\sqrt{3}}{2})[/tex]


Register to reply

Related Discussions
Solution of two first order differential equation with one algebraic equation. Differential Equations 2
Order of a Differential Equation Calculus & Beyond Homework 1
2nd order differential equation using reduction of order Calculus & Beyond Homework 7
Differential equation - 2nd order diff equation Calculus & Beyond Homework 5